Методи реалізації багатокритеріальних бізнес-моделей мультимодальних транспортних підприємств - Гончаров, Артем; Могілей, Сергій (Kamianets-Podilskyi National Ivan Ohiienko University, 2021)
Under globalizing processes in the international economy, the problem of perfect logistics in commercial projects is quite urgent. It's foremostly important in big business structures, transnational corporations and other economic structures in Ukraine and abroad. Logistics in this case would surely suggest numerous means of transportation. Multimodal logistics means are especially important as they mean simultaneous or parallel employment of several transportation means. Besides, the investigation is concentrated on the optimization criteria of multimodal transportations, which enables to formulate the current model as a multicriteria optimization problem. The writing considers several methods for this problem solution, with their application. Applying special programming means for the business model is as well described. The business model is designed universally, which enables it to extend the result within the whole class of analogous models without alternating the algorithm of solution. So the object of the investigation is a business model of a multimodal logistics company and the focus is on methods of its solution. Its objective is to determine various methods to solve multicriteria optimization problems in transportation logistics. The paper demonstrates the most effective of all methods suggested and signifies the algorithm to solve the two-criteria multimodal logistics problem. To illustrate the algorithm, both real and model data are provided.